The great American university : its rise to preeminence, its indispensable national role, why it must be protected - Cole, Jonathan R. (PublicAffairs, 2009)
"Americans and people throughout the world have become increasingly dependent on America's great research universities. Yet few of us truly understand to what we owe this extraordinary excellence or what we must do to keep it." "From the development of technologies like the laser, the global positioning system, the MRI, radar, and even Viagra, to predicting weather patterns, American research universities are one of our most vital sources of economic growth and social welfare. They have flourished because of a system that has invested public tax dollars in their work and, more importantly, granted substantial autonomy to funding agencies and the universities." "This system is now under attack, the university's preeminence endangered by the USA Patriot Act and other conservative policies. This revelatory and alarming book will show how this vital institution is at risk of tragically losing its dominant status and why a threat to the university is a threat to the health and wealth of our nation."--Jacket